Keragaman Jenis Amfibi dan Reptil Gumuk Pasir, Propinsi Daerah Istimewa Yogyakarta - Qurniawan, Tony Febri (Masyarakat Zoologi Indonesia (Zoological Society of Indonesia), 2013)
Sand dune (gumuk pasir) in Yogyakarta is an area that has a unique ecosystem eolian. It is very interesting to study the species diversity of amphibians and reptiles in that area. The research was done since October-December 2008 and March-May 2009 to uncover the species diversity of reptiles and amphibians in sand dune. The total numbers of herpetofauna are 14 species of 3 amphibians and 11 reptiles. The common species found are Hemidactylus frenatus (38.8%) and Duttaphrynus melanostictus (31.5 %). We also recorded the presence of snake-eyed skink Cryptoblepharus cursor which is adapted to the littoral habitat very well.